CostMAP: an open-source software package for developing cost surfaces using a multi-scale search kernel. Issue 3 (3rd March 2020) - Hoover, Brendan; Yaw, Sean; Middleton, Richard
ABSTRACT: Cost surfaces are a crucial aspect of route optimization and least cost path (LCP) calculations and are used in awide range of disciplines including computer science, landscape ecology, and energy-infrastructure modeling. Linear features present akey weakness to traditional routing calculations along cost surfaces because they cannot identify whether moving from acell to its adjacent neighbors constitutes crossing alinear barrier (increased cost) or following acorridor (reduced cost). Following and avoiding linear features can drastically change predicted routes. We introduce an approach to address this adjacency issue using asearch kernel that identifies these critical barriers and corridors. We have built this approach into anew Java-based open-source software package–  CostMAP  (cost surface multi-layer aggregation program)– which calculates cost surfaces and cost networks using the search kernel.  CostMAP  allows users to input multiple GIS data layers and to set weights and rules for developing aweighted-cost network. We compare  CostMAP  performance with traditional cost surface approaches and show significant performance gains– both following corridors and avoiding barriers– by modeling the movement of alarge terrestrial animal– the Baird's Tapir ( Tapirus bairdii )– in amovement ecology framework and by modeling pipeline routing for carbon capture and storage (CCS).